PENGARUH PROPORSI GULA PASIR DAN GULA AREN PADA KARAKTERISTIK CREAMCHEESE CAKE SETELAH SATU MINGGU PENYIMPANAN BEKU - Erlienawati, Tabitha Christina; Suseno, Thomas Indarto Putut; Setijawati, Erni (Jurnal Teknologi Pangan dan Gizi, 2017)
Creamcheese cake is an innovation of chiffon cake that has sweet taste, soft, light, soft texture and moist characteristics. Creamcheese cake stored in a frozen storage will have a tougher texture and more rough. Tough and rough texture is influenced by sugar, so it needs to be added alternative ingredients to improve creamcheese cake texture. Palm sugar is a tradisional sugar that can be used as an ingredient in cakes. Palm sugar contains invert sugar more than sugar, so creamcheese cake still has a soft texture and moist. The proportion of sugar and palm sugar can be affected in several factors of creamcheese cake, including the physicochemical and organoleptic properties of creamcheese cake product. The methodology of this research is a randomized block design (RBD) with one factor, that is the proportion of sugar and palm sugar (P), which consists of seven levels 100%:0% (P1), 95%:5% (P2); 90%:10% (P3); 85%:15% (P4); 80%:20% (P5); 75%:25% (P6); dan 70%:30% (P7) of sugar used. Repetition of the experiments are carried out four times. The proportion of sugar and palm sugar effected the water content, specific volume, texture (hardness, cohesiveness, gumminess, springiness), color, and organoleptics (color, taste, softness, moistness, pore uniformity). The increasing of the proportion of palm sugar could increase the value of water content, hardness, cohesiveness, gumminess, redness and decrease the value of specific volume and lightness, yellowness, and chroma. The best treatment that determined by spider web method in creamcheese cake is the proportion of sugar and palm sugar 95%: 5% which had moisture content value 34.59%,specific volume 1.7381 cm3 / g, hardness 1457.684 g, cohessiveness 0.311, Gumminess 455.048, springiness 0.527 g, and favorite panelist level of taste parameter 6.6444, color 6.222, softness 7.2000, moistness 6.8667, and pore uniformity 6.9111 with score 1-9 as standard, creamcheese cake with the proportion of sugar and palm sugar 100%: 0% is considered as control.